2008
DOI: 10.1177/0898264308324652
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Gender and Religiousness on Alzheimer Disease Caregivers' Use of Informal Support and Formal Services

Abstract: Objective-This study explored how male and female family caregivers of Alzheimer's disease (AD) patients differ in their use of formal services and informal support and how religiousness may affect such differences.Methods-Data were from a sample of 720 family caregivers of AD patients who participated in the Resources for Enhancing Alzheimer's Caregiver Heath (REACH I) study sites in Birmingham, Boston, Memphis, and Philadelphia.Results-Female caregivers were less likely to use in-home services than males (M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 43 publications
2
38
1
Order By: Relevance
“…With the exception of one study (Sun et al, 2008) all employed qualitative methods. The findings will be reported in relation to four subthemes: men's constructions of caregiving as men's work, the "man-made" challenges of caregiving, men's help-seeking experiences, Gender-based social networks highly influenced the men's masculine identities.…”
Section: Men's Experiences Of Caregivingmentioning
confidence: 99%
“…With the exception of one study (Sun et al, 2008) all employed qualitative methods. The findings will be reported in relation to four subthemes: men's constructions of caregiving as men's work, the "man-made" challenges of caregiving, men's help-seeking experiences, Gender-based social networks highly influenced the men's masculine identities.…”
Section: Men's Experiences Of Caregivingmentioning
confidence: 99%
“…However, men have reported the use of some types of formal support (e.g., homemaking, transportation) (Brazil et al, 2009; Schwartz, 2013; Sun, Roff, Klemmack, & Burgio, 2008). To the authors’ knowledge, the help-seeking behaviors of men couched in contemporary understandings of the socialization of gender and the meaning of masculinity remain understudied, and are warranted to gain a more holistic picture of men’s acceptance of formal supports.…”
Section: Formal and Informal Service Use By Male Caregiversmentioning
confidence: 99%
“…The review of literature for measures of caregiver use of resources identified three theories used in studying caregiver's use or non-use of services. The theories were Pearlin's Coping Stress Model (Sun, Roff, Klemmack, & Burgio, 2008), Andersen's Behavioral Model of Service Use (Phillipson et al, 2014), and the Theory of Planned Behavior with Andersen's Behavioral Model of Service Use (Phillipson et al, 2013). Andersen's model was APPCGNONUSESERVICES 28 chosen to guide this study because this theory addressed the characteristics that could potentially impact service use or non-use in Appalachian healthcare systems.…”
Section: Caregivers and Use Of Services For Persons With Dementiamentioning
confidence: 99%
“…The SPS was the most frequently used instrument to assess CG use of resources in the recent literature (Robinson, Buckwalter et al, 2005;, however the scale was not adequate for assessing all variables of interest in Andersen's model, or identifying important information suggested from the review of literature (Brown, Chen, Mitchel, & Province, 2007;Johnston et al, 2011;O'Connell et al, 2012;Phillipson et al, 2014;Phillipson et al, 2013;Phillipson & Jones, 2012;Phillipson & Jones, 2011;Ploeg et al, 2009;Robinson, Buckwalter et al, 2005;Robinson et al, 2012;Robinson et al, 2013;Stockwell-Smith et al, 2010;Sun et al, 2008). Table 4 in Appendix F connects the literature review to the expanded SPS questions.…”
Section: Expanding the Social Provision Scale (Sps)mentioning
confidence: 99%
See 1 more Smart Citation